2019
DOI: 10.3390/ma12111829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wetting–Drying Cycles on the Mechanical Properties and Microstructure of Wood Waste–Gypsum Composites

Abstract: Large amounts of wood waste are generated each year in the world. In an attempt to identify a good recovery option for those residues, wood waste from construction and demolition works were used as raw materials in gypsum plasters. However, wood is a biodegradable material which implies that the products or materials that contain it are susceptible to suffering an important deterioration, due to exposure in certain environments. For that reason, the aim of this work was to simulate the effects that, in the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…These different characteristics will also affect chemical and physical interactions with other mortar components, thus influencing mechanical properties. This tendency for a decrease in mechanical properties with the addition of biomass was already observed by other authors [41,42]. Morales-Conde [43] found that not exceeding 5% of sawdust incorporation on gypsum mortars led to an improvement of flexural strength, whereas all the percentages of sawdust additions decreased the compressive strength.…”
Section: Flexural and Compressive Strengthsupporting
confidence: 74%
“…These different characteristics will also affect chemical and physical interactions with other mortar components, thus influencing mechanical properties. This tendency for a decrease in mechanical properties with the addition of biomass was already observed by other authors [41,42]. Morales-Conde [43] found that not exceeding 5% of sawdust incorporation on gypsum mortars led to an improvement of flexural strength, whereas all the percentages of sawdust additions decreased the compressive strength.…”
Section: Flexural and Compressive Strengthsupporting
confidence: 74%
“…Lignin is a heterogeneous compound consisting of the elements carbon (C), hydrogen (H), and oxygen (O). In contrast to cellulose, which is formed from carbohydrate groups, lignin is formed from an arrangement of aromatic groups linked to each other by aliphatic chains [22,23]. The carbonyl content is very dominant in the aromatic group.…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…Waste wood in the use of wood chips to replace fine aggregates in the preparation of mortar and concrete found that with the increase in the amount of wood chips doped wood chips and the interface between the pulp increases, the density of the concrete was gradually reduced, the compressive strength was gradually decreased, the drying shrinkage was diminished, and the resistance to cracking ability was enhanced. Among them, when the proportion of wood chips substitution was 10%, the compressive strength was reduced by about 10%; when the proportion of substitution was 60%, the compressive strength is reduced by about 40% [20][21][22][23][24]. Whereas, the preparation of wood fiber-based concrete using waste wood found that wood fiber addition can significantly increase the mechanical strength of concrete, especially the flexural strength.…”
Section: Introductionmentioning
confidence: 99%